Appropriating national curriculum standards in classroom teaching: Experiences of novice language teachers in China. (2017) - Yuan, Rui
Highlights: Novice teachers try to appropriate curriculum standards in their teaching. Their self-agency guides their appropriation of curriculum standards. Their appropriation is influenced by their situated activity systems. They should be equipped with mediational tools in curriculum appropriation. Abstract: Drawing on an activity theory perspective, this study explores how a group of novice English teachers (n = 285) appropriated the national curriculum standards in the first year of their teaching. The findings revealed the disparity among the participants with respect to when, how, and why they appropriated the curriculum standards in their professional work. Such differences resulted from the complex interactions between the participants' professional competence and self-agency as well as various institutional (e.g., collegial support and school culture) and socio-cultural factors (e.g., the exam-oriented system). This study generates practical implications for both pre- and in-service teacher education on how to help language teachers close the gap between the espoused curriculum and their classroom teaching and seek their continuous professional development.